Public procurement as a complex object for management accounting in public sector - V.O. Psota (Економіка, управління та адміністрування, 2020)
In connection with the implementation of budget accounting and public procurement according to international standards, the importance of management accounting in the public sector is enhanced. This especially affects the efficiency of the use of public finance in procurement. The article considers public procurement as a complex object of accounting, which consists of interrelated objects: the subject and the procurement procedure, consisting of elements. The paper focuses on each element, highlights the features of their use in public procurement in accordance with current legislation and suggests the ways to improve the operation of electronic systems in terms of determining the subject of procurement. The analysis of the use of procurement procedures for each element of the subject of procurement is carried out and the need to consider these objects as a whole in order to make management decisions on the use of budgetary funds is proved. The paper highlights the stages of public procurement and proves the importance of a comprehensive public procurement facility at each stage of the tendering process in order to monitor, control and ensure the efficient use of public finances.